A novel fabrication of organic-inorganic hybridized Graphene-La2CrFeW6 nanocomposite and its improved photovoltaic performance in DSSCs - Won‐Chun Oh; Yin Liu; Yonrapach Areerob (Journal of Science Advanced Materials and Devices, 2021)
We fabricated a novel nanocomposite composed of graphene-La2CrFeW6 perovskite compounds with an organic-inorganic counter electrode based on CdSe, gallic acid, urea and sulfate in dye-sensitized solar cells (DSSCs) by a simple hydrothermal technique. The nanocomposite shows an excellent electro–catalytic activity with low charge-transfer resistance, due to the synergetic catalytic effects of the graphene sheets and La2CrFeW6 perovskite with organic-inorganic materials. The special structure of this nanocomposite also improves the active sites for reduction of triiodide ions on the counter electrodes. The photo-conversion efficiency of the DSSC fabricated using a gallic-based counter electrode reached a higher value of 10.40% under standard illumination (1 sun, 100 mW cm−2, AM 1.5), as compared to the traditional Pt electrode (7.49%). The graphene-La2CrFeW6 fabricated with an organic-inorganic based CE was also found to be more efficient than those reported in previous works, in which graphene, produced by various methods, was used as a CE material. Therefore, the present nanocomposite is considered an environmentally friendly, low-cost, and highly efficient CE material for DSSCs.
Keywords: Advanced Photocatalysis Techniques; TiO2 Photocatalysis and Solar Cells; Perovskite Materials and Applications